2021
DOI: 10.1186/s40813-020-00187-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of space allowance and mixing on growth performance and body lesions of grower-finisher pigs in pens with a single wet-dry feeder

Abstract: Background Low space allowance (SA) and mixing may result in reduced growth performance (GP) and animal welfare issues because of adverse social behaviours directed to pen mates. This could be exacerbated in pens with single space feeders owing to social facilitation of feeding behaviour. The present study aimed to investigate the effect of SA and mixing on GP and body lesions (BL) in pens with one single space wet-dry feeder. Results Two experimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 46 publications
4
25
1
Order By: Relevance
“…Lambs in the LSA group also suffered more aggressions when lying compared to the C group. This increased aggressivity is in agreement with results in cattle [ 39 ], pigs [ 40 ], and camels [ 41 , 42 ] kept at limited space allowances. Although aggressive behaviors have been rarely observed among female sheep kept on pasture [ 43 ], limited resources such as restricted area shelter have been found to enhance aggressive behaviors also in sheep [ 30 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Lambs in the LSA group also suffered more aggressions when lying compared to the C group. This increased aggressivity is in agreement with results in cattle [ 39 ], pigs [ 40 ], and camels [ 41 , 42 ] kept at limited space allowances. Although aggressive behaviors have been rarely observed among female sheep kept on pasture [ 43 ], limited resources such as restricted area shelter have been found to enhance aggressive behaviors also in sheep [ 30 , 44 , 45 ].…”
Section: Discussionsupporting
confidence: 90%
“…Pigs are subjected to several stressors in the production system including space restriction during the finishing phase. It has been documented by numerous studies that reduced floor space results in reduced growth performance ( Flohr et al, 2016 ; Johnston et al, 2017 ; Thomas et al, 2017 ; Carpenter et al, 2018 ; Lei et al, 2018 ; Wastell et al, 2018 ; Lerner et al, 2020 ) and increase the incidence of abnormal behavior, including aggression, and tail biting ( Anil et al, 2007 ; Montoro et al, 2021 ). However, the negative outcome of increased prevalence of skin lesions in low space allowance conditions has not been observed in all studies as shown by Johnston et al (2017) .…”
Section: Discussionmentioning
confidence: 99%
“…Mixing is a common management strategy used to sort pigs by weight in order to decrease BW variability and facilitate farm management practices. However, previous research stated that mixing fails to reduce final BW variability in individual pig weights within a pen [11,12], and that it may affect growth performance [13][14][15] and pig welfare due to the establishment of a new social hierarchy after re-grouping [16].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported findings on the effects of SA and PF on growth performance in grower-finisher pigs [1,4,22]. However, very little attention has been paid to the role of mixing on productive performance in grower-finisher pigs over the last two decades [13][14][15]. Moreover, there has been little discussion about how SA and mixing or whether SA and PF interact with each other in field conditions [13,15].…”
Section: Introductionmentioning
confidence: 99%